Sistem Pendaftaran Peserta Didik Baru pada SMK Berbasis Web Menggunakan Metode Waterfall - Zulham Iftikar Jamaludin; Andri Firmansyah; Ikhsan Romli (STMIK Budi Darma, 2023)
Education is one of the critical sectors in the development of a country, and the need for an efficient new student registration process has become increasingly pressing with technological advancements. a vocational high school in North Cikarang, currently faces challenges in the manual process of enrolling new students. This creates issues for prospective students and school administrators. To address this problem, a technology-based solution is required, and the use of the Waterfall method in system development is an appropriate approach. The Information System for New Student Enrollment at Vocational High School, using the Waterfall method, aims to provide an efficient, structured, and accessible registration process. With this approach, each step in the system development process is carried out sequentially, including analysis, system design, implementation, testing, and maintenance. Prospective students and parents can access this system online, eliminating geographical limitations in the registration process. The results of this research include the development of a web-based new student registration system using PHP with the Laravel framework. This system provides a solution to address the existing manual issues at Vocational High School. In conclusion, this system offers several benefits, including simplifying the registration process for parents, providing better access to school information, and improving the efficiency and effectiveness of the new student admission process. Furthermore, data stored in the database is more secure and easily accessible to school staff.